Chemical characterisation of total suspended particulate matter from a remote area in Amazonia - Goncalves, Catia; Figueiredo, Bernardino R.; Alves, Celia A.; Cardoso, Arnaldo A. [UNESP]; Silva, Rodrigo da; Kanzawa, Simone H.; Vicente, Ana Margarida (Elsevier B.V., 2016)
This research had as study object the total suspended particulate matter collected in the Alenquer region, a remote area in the Para state. The main objectives were the characterisation of the inorganic and organic chemical composition of the aerosol, looking for seasonal patterns and the identification of probable emission sources and formation processes. A set of 30 samples were collected in the rainy (April-May) and dry season (August-September) of 2014. The analytical methods included gravimetric analysis, water-soluble ions analysis by ion chromatography (IC), elemental analysis by inductively coupled plasma mass spectrometry (ICP-MS) equipped with collision cell technology, carbonaceous content determination with a thermal-optical system and organic speciation by gas chromatography-mass spectrometry (GC-MS). The average concentrations of particulate matter ranged from 14 +/- 13 mu g.m(-3) to 31 +/- 7.8 mu g.m(-3), in the rainy and dry season, respectively. The carbonaceous content represented, on average, approximately 27% and 21% of the particulate matter in the rainy and dry season, respectively. Na+, Cl-, SO42-, and NO3- yield the highest concentrations in both seasons. Na was the dominant element, reflecting the transport of air masses from the Atlantic. An increase in concentrations between the rainy and dry seasons was especially noted for the terrigenous elements such Mn, Fe and Al. The chromatographically resolved organics included n-alkanes, n-alkenes, PAHs, n-alkanoic acids, n-di-acids, resin acids and some phenolic compounds. The primary inputs of organic constituents to the aerosols of Alenquer based on the homologous compound series and biomarkers were: (i) natural emissions from terrestrial higher plants waxes, particularly in dry season; (ii) anthropogenic emissions from diesel fuel combustion and biomass combustion, predominating during the dry season. The chemical characterisation along with the backward trajectory cluster analysis suggests a great influence from natural sources such as marine aerosol, mainly in the rainy season. In the dry season, the region is also affected by soil dust re-suspension and some biomass burning. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Water-soluble ions; Elements; Organic speciation; TSP; Amazonia